Pigeon pea refuge crops are likely to provide patchy delivery of Helicoverpa (Lepidoptera: Noctuidae) within Bt cotton production regions in eastern Australia. Issue 4 (20th May 2016) - Baker, Geoff H.; Parry, Hazel; Tann, Colin R.
Abstract: Refuge crops, in particular pigeon pea and conventional (non‐Bt) cotton, are mandatory components within the Bt resistance management strategy for Helicoverpa pests in Bt cotton production systems in eastern Australia. These refuge crops are expected to produce large numbers of Bt‐susceptible moths, some of which will mate with the relatively few resistant moths emerging from Bt cotton, thus reducing the likelihood of Bt resistance developing. The spatial and temporal variability in Helicoverpa production in pigeon pea refuge crops within the St George Irrigation Area in southern Queensland was measured in this study, and the likely dispersal of moths produced in such refuges to Bt cotton crops throughout the local landscape was modelled. The attractiveness of pigeon pea for Helicoverpa oviposition and the resultant abundance of eggs on plants and pupae in the soil were highly variable between refuge crops within and between seasons. A simulation model was developed to explore the effects of random and wind‐biased assumptions on moth movements within the landscape. The model was initialised using data on the abundance of either live pupae or remains of pupal cases in the soil as surrogates for moth production within refuges. The results of the model suggested that delivery of moths from refuges to Bt cotton crops throughout the St George landscape would be patchy, with some areas thus more likely to be exposed to the threat of Bt resistance development than others. A reduction in refuge area requirements, such as recently proposed as a change to the Bt resistance management guidelines, appears likely to exacerbate such risk.